A systemic approach for trade-off analysis of food loss reduction and greenhouse gas emissions - Guo, Xuezhen; Broeze, Jan; Axmann, Heike; Vollebregt, Martijntje (2019)
This paper introduces the Agro-Chain Greenhouse Gas Emissions (ACGE) calculator, a calculator for estimating GHG emissions for food supply chains that addresses emissions due to agricultural production and post-harvest activities. The calculator combines direct emissions of GHGs by the activities in the chain and effects due to losses, differentiated for 5 stages along the chain. One of the major challenges of analyzing a chain is data collection. In many practical situations only a limited set of (primary) data is available. In order to facilitate the use, the calculator is supplemented with a complete set of secondary data: crop GHG emission factors aggregated at product category level and FLW estimates per chain stage, aggregated at product category level; all data differentiated for 7 global regions. The tool is highly suitable for assessing net GHG emission effects of food loss and waste (FLW) reducing interventions: comparing different chain configurations, each with adequate FLW estimates. Through two intervention analysis examples it is shown that not only agricultural production but also post-harvest chain adds significant emissions to the food supply. The FLW-reducing intervention considered adds substantial extra emissions. In one example the FLW-reduction has larger GHG emission reduction effects, but in another example the extra emissions are higher than the prevented emission from lower food losses. Consequently the intervention is not an effective GHG emission reduction intervention. We recommend to use this approach for climate-smart FLW reduction intervention prioritization.